Covalently cross-linked tetrafunctionalized m-THPC chitosan hydrogels as drug delivery platforms - Gierlich, Piotr (2022)
5,10,15,20-Tetrakis(3-hydroxyphenyl)chlorin (m-THPC, temoporfin), is a second generation PS that has been available on the market for over two decades under the commercial name Foscan. Practical limitations of PDT with Foscan are reflected in patient discomfort due to prolonged skin photosensitivity which causes skin burning and inflammation. Therefore, there is a constant need for the development of new pharmaceutical formulations that will allow these drawbacks to be overcome and improve quality of life for cancer patients. This body of work outlines the design of tetrafunctionalized m-THPC derivatives which exhibit improved photophysical and biological properties in comparison with the parent compound. We detail DDS s, specifically hydrogels, capable of controlling drug release through response to the altered pH of the tumor microenvironment. Hydrogels were produced, characterized, and tested under biological conditions with the results described across experimental chapters 2- 5. Chapter 1 provides a general introduction to Photodynamic Therapy (PDT) and highlights the importance of the immune system response for successful treatment of cancer. We explain the major drawbacks related with the clinical use of Foscan and highlight the advantages of hydrogels as promising platforms for delivery of hydrophobic molecules. Chapter 2 focuses on synthetic strategies towards tetrafunctionalization of m-THPC derivatives. This approach aims to append different functionalities at the periphery which allows their use as suitable synthetic handles for the design of drug delivery platforms. For this, reliable, cost-efficient synthetic strategies were employed. Substitution, esterification, and Sonogashira coupling reactions produced tetrafunctionalized derivatives PS 1, 3 and 5. The next part of this chapter focuses on the evaluation of the linear optical properties of m THPC derivatives, including determination of their fluorescence quantum yield (ΦF), fluorescence lifetime (τ) and singlet oxygen quantum yield (ΦΔ). Finally, we assess the impact of substitution of m-THPC periphery for enhancement of non-linear properties of the dye using the two-photon excited fluorescence (TPEF) technique. iii Chapter 3 highlights the synthesis and characterization of covalently cross-linked chitosan (CS) hydrogels formed by the reaction of CS chains with tetrafunctionalized m-THPC derivatives and difunctionalized PEG via amide and/ or imine bonds. Next, we provide rheological and macroscopic evaluation of the rheological properties of the obtained formulations. Finally, part of this chapter demonstrates a sustained release of the encapsulated PS upon decrease in pH. Mediation of this release is anticipated to be a result of progressive cleavage of the cross-link bonds between the CS and the PS. Evaluation of the activity of tetrafunctionalized m-THPC derivatives in vitro against B16F10 and CT26 cancer cells with comparison to the activity to m-THPC is provided in chapter 4. For this we employ intra- and extracellular PDT protocols. The main mechanism of the extracellular phototoxicity was found to be caused via lipid peroxidation and confirmed by two methods – flow cytometry and confocal imaging using a ROS-sensitive BODIPY 581/591 probe. The final part of this chapter focuses on the determination of the primary cell death mechanism triggered by the activity of water-soluble derivative PS 3. The last experimental section of this doctoral thesis, chapter 5, provides in vivo evaluation of the phototoxic activity of the lead derivative, PS 3, formulated and applied as a CS-based formulation. Intratumorally injected hydrogel formulations were applied towards CT26 colon carcinoma and B16F10 melanoma tumors. Moreover, we provide evaluation of the PS biodistribution using an in vivo fluorescence technique. Due to the prolonged release of the PS from the hydrogel at the site of injection, we compare the therapeutic efficacy upon two, single and multiple irradiation protocols. The final part of the thesis explores PDT-induced activation of the immune system via three protocols: 1) rechallenge of cured animals two months after PDT treatments, 2) evaluation of abscopal effects on a pseudo-metastatic model, and 3) evaluation of the PDT activity in immunocompetent versus immunocompromised mice.